Human papillomavirus infection and cervical neoplasia among migrant women living in Italy - Tornesello, Maria Lina; Giorgi Rossi, Paolo; Buonaguro, Luigi; Buonaguro, Franco M. (Frontiers in Oncology, 2014)
Human papillomavirus (HPV) infection is highly prevalent in women migrating from countries where cervical screening is not implemented. The variety of HPV genotypes, their prevalence and the association with cervical abnormalities has been investigated by several groups in women moving mainly from Eastern Europe, Africa and Southern Asia to Italy. All studies are concordant on the elevated rate of HPV infection among immigrants which is four times higher than that observed among age-matched Italian women. The HPV prevalence among short-term migrants and characterization of viral variants showed that the high prevalence of HPV reflects either individual lifestyle or high prevalence of HPV in the country of origin. The high burden of HPV infection correlates very well with the high incidence of cervical cancer in migrant women. In fact, during the years 2000–2004 the cervical cancer incidence in women from Central and Eastern Europe and living in Central Italy was 38.3/100,000 which is statistically significant higher than that of native Italian women (6 per 100,000). In this study we pooled together the results of three independent studies originally designed to assess the distribution and the prevalence of HPV genotypes among 499 immigrant women living in Southern Italy. A total of 39 mucosal HPV genotypes were identified. The 12 genotypes (HPV16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58 and 59) classified as carcinogenic to humans (group 1) accounted for >80% of all infections. HPV16 was the most common viral type in all groups with frequency rates ranging from 15.4% in Africa to 51.1% in Eastern & Southern European HPV-positive women. The high prevalence of oncogenic HPVs and cervical cancer risk among migrant women, together with the lower participation in screening programs, demands for an urgent implementation of preventive strategies to increase screening and vaccine coverage and viral monitoring of uncommon HPV genotypes potential spreading in settled populatio